Effect of geosynthetic reinforced embankment on locally weak zones by numerical approach. (April 2015) - Benmebarek, Sadok; Berrabah, Fouad; Benmebarek, Naïma
Abstract: This paper presents a numerical simulation using PLAXIS code of geosynthetic reinforced embankment over locally weak zones. The case study concerns the reinforcement of the road embankment which crosses a section of about 11 km on sabkha soil of Chott El Hodna in Algeria. This salt flat is dry in summer but gets flooded in winter. The site observations and the geotechnical investigations indicated that the soil of this sabkha is characterised by high compressibility, low bearing capacity and contains locally weak zones of limited extent. The main objective of this paper is to assess the effect of geosynthetic reinforcement on the settlement of the embankment over locally weak zone. The influence of some parameters, namely the compressibility parameter of locally weak zone, the stiffness of geosynthetic, the locally weak zone geometry and the friction angle of embankment fill is also analysed. The results show that the computation with large displacement is more suitable than small displacement for this problem and the differential settlement improvement is due to the combination of the membrane strength effect of the geosynthetic and the arching effect within the embankment fill.